Use of yeast and its derived products in laying hens: an updated review. Issue 4 (2nd October 2022) - Bilal, Rana Muhammad; Elwan, Hamada A. M.; Elnesr, Shaaban S.; Farag, Mayada R.; El-Shall, Nahed A.; Ismail, Tamer A.; Alagawany, Mahmoud
SUMMARY: Antibiotics have been widely used in the poultry sector to improve production performance, but this has resulted in consumer health concerns. Growing demand for organic products has prompted scientists to develop new methods and materials in the poultry industry. These include the use of medicinal plants or beneficial microorganisms. If properly and legitimately selected and exploited, the future for probiotics and prebiotics appears to be very strong for the poultry industry. Organic or natural feed additives have been found to be more effective than many of the antibiotic growth promoters in reducing the load of harmful gastrointestinal pathogens. The use of probiotics in a daily supplementation regimen has become a popular routine method in the commercial poultry industry. One of the most important microorganisms used since ancient times are yeast and its derivatives. Yeasts play a key role in many complex ecosystems and engage in parasitic, symbiotic, and antagonistic relationships with other microbes. Yeast contains biologically essential proteins, vitamin B-complex, mannan oligosaccharide, B-D-Glucan, vital trace minerals, carotenoids, and numerous unexplained growth-promoting substances. The combination of these nutritional metabolites increases poultry health by balancing the immune system while boosting gut health and nutrient digestibility. Due to prohibitions on the use of antimicrobial growth promoters in many countries, these yeast-based products are replacing additives in chicken feed since they have certain health and nutritional benefits. In several studies, incorporating yeast into diets improved nutrient utilisation and boosted egg weight and egg production in layer chickens. In this review, we will discuss the uses of yeast in laying hen nutrition as an alternative way for organic poultry production instead of traditional growth promoters.